Studi Tentang Kendala-Kendala yang Dihadapi oleh Kantor Akuntan Publik dalam Melakukan Merjer - Sawarjuwana, Tjiptohadi; Mayasari, Triana (Journal of Accounting and Investment, 2015)
A merger is considered to be one of powerful business strategies that provides several benefits. Among others are an accumulated capital, a synergic management, a wide market, and become a bigger company. In accounting firm realm, a service industry, merger promeses the fundamental human capital, indeed, the accumulated profesional skills, knowledge and abilities. However, not much accounting firms take this promising strategic. It is a research that delves to uncover the rational beyond the reasons why they are reluctant to take that excellent chance. By conducting an indepth interview method, this research interviewed some accounting firms, particularly those who take that opportunity, who are in progress, who do not. This method enables the researcher to have a very comprehensive understanding about the various reasons underlying merger. 32 managing partners or partners of some accounting firms took part this research. They run their business in Jakarta, Yogyakarta and Surabaya. The research comes to conclude that the main hurdle of doing merger is a curtural problem. The other difficulties are the starting point of a merger, the basic to determine their assets and clients, and worry about the melting process. However, these rational are being ignored by those who have done the merger. They contend that those obstacles will naturaly be overcome by the time